Scope of Data Journalism for Investigation Reporters in Pakistan - Dr. Taha Shabbir; Imran Arif; Saeed Memon; Mohsin Wazir; Zafar Siddiqui (International Journal on Human-Computing Studies, 2021)
Data Journalist can be defined as Journalists who work with numbers "a method of optimizing analysis and news coverage through the use and review of information in order to offer a deeper understanding of a news story and to draw attention to pertinent facts. One trend in journalism's digital age has been to disseminate knowledge to the public through interactive web content created using data visualization tools such as tables, graphs, charts, infographics, microsites, and visual worlds. In-depth analysis of certain data sets may result in more detailed conclusions and assumptions about current hot topics. Additionally, data journalism will shed light on previously unrecognized topics that were ostensibly ignored by the news media. With the invention of knowledge and communication technologies, our ways of living and communicating, making decisions, and knowing reality have been revised. By adding a quantitative portion, the fundamental tenet of existence is altered. By incorporating computational thinking into newsrooms, the traditional logic of journalism has been fundamentally altered. Additionally, the linear narration was altered to provide a more engaging and enjoyable experience. Access to troves of open data enables one to understand, explain, and express reality in the digital era.